Determinants of Household Clean and Healthy Living Behaviour (PHBS) in Kelurahan X, Sidoarjo, East Java - Qudrad Anugerah, Farhan; Mahyaya, Maisya Icha; Qurrota A’Yunin Al Isyrofi , Atik; Ibad , Mursyidul (Jurnal Kesmas Jambi, 2026)
Clean and Healthy Living Behaviour (PHBS) is an important indicator for improving public health; however, its implementation at the household level remains suboptimal and is influenced by individual and environmental factors. This study aimed to identify the determinants of PHBS among communities in Kelurahan X, Sidoarjo, East Java in 2025. A quantitative cross-sectional study was conducted among 449 respondents selected using stratified random sampling. Data were collected using a structured questionnaire and analyzed using binary logistic regression. The proportion of households with good PHBS was 85.1%. Productive age (OR = 5.70; 95% CI: 2.36 to 13.75), higher economic status (OR = 72.74; 95% CI: 6.23 to 849.96), ownership of wastewater disposal systems (SPAL) (OR = 35.55; 95% CI: 9.07 to 139.33), household latrine ownership (OR = 15.25; 95% CI: 6.32 to 36.78), and septic tank ownership (OR = 28.16; 95% CI: 2.03 to 89.89) were identified as significant determinants of PHBS. The condition of the wastewater disposal system was the dominant factor of PHBS after adjustment for other variables. Therefore, strengthening household sanitation, particularly by improving wastewater disposal systems, expanding access to sanitary latrines and septic tanks, and enhancing community-based health promotion programs, should be prioritized to improve PHBS implementation.